Hak-Hak Istri Pasca Penceraian dalam Sistem Hukum Islam, Sistem Hukum Anglo Saxon, dan Sistem Hukum Erofa Kortinentel - Fu’ad, Asep; Ah. Fathoni; Rasyid, Fauzan Ali (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
The rising trend of divorce has brought significant attention to the protection of women’s rights after marital dissolution. This study explores and compares how Islamic Law, Anglo-Saxon Law, and Continental European Law regulate post-divorce rights such as maintenance during ‘iddah, mut’ah compensation, joint property division, and child custody. Employing a normative-juridical and comparative approach through library research, the study examines primary and secondary legal sources. The findings reveal that Islamic Law emphasizes spiritual and social justice grounded in maqāṣid al-sharī’ah; the Anglo-Saxon system relies on judicial discretion to adapt to individual circumstances; while the Continental European system focuses on legal certainty through codified statutes. Each system presents unique strengths and challenges in ensuring protection for divorced women, particularly in addressing patriarchal practices, legal access disparities, and emotional needs. The study advocates for an interdisciplinary and integrative approach that synthesizes the strengths of all three systems to foster a more equitable, gender-sensitive, and contextually relevant legal framework for post-divorce women’s rights.